2016
DOI: 10.1111/eva.12380
|View full text |Cite
|
Sign up to set email alerts
|

What, if anything, are hybrids: enduring truths and challenges associated with population structure and gene flow

Abstract: Hybridization is a potent evolutionary process that can affect the origin, maintenance, and loss of biodiversity. Because of its ecological and evolutionary consequences, an understanding of hybridization is important for basic and applied sciences, including conservation biology and agriculture. Herein, we review and discuss ideas that are relevant to the recognition of hybrids and hybridization. We supplement this discussion with simulations. The ideas we present have a long history, particularly in botany, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 149 publications
(301 reference statements)
3
123
0
Order By: Relevance
“…On island systems, the evolutionary forces of hybridization and gene flow have been thought to play important roles in the diversification of lineages, though the underlying processes are not well understood (Yoder et al, ; Ellstrand et al, ). HTS methods and modern genomic tools provide new avenues to test for the effects of hybridization in diversification (Gompert & Buerkle, ; Payseur & Rieseberg, ; Vallejo‐Marín & Hiscock, ). Here, we use targeted enrichment strategies implemented through Hyb‐Seq (Weitemier et al, ) to demonstrate its utility in understanding phylogenetic relationships of Hawaiian Cyrtandra, and to test morphologically‐based hypotheses of gene flow in this lineage.…”
Section: Discussionmentioning
confidence: 99%
“…On island systems, the evolutionary forces of hybridization and gene flow have been thought to play important roles in the diversification of lineages, though the underlying processes are not well understood (Yoder et al, ; Ellstrand et al, ). HTS methods and modern genomic tools provide new avenues to test for the effects of hybridization in diversification (Gompert & Buerkle, ; Payseur & Rieseberg, ; Vallejo‐Marín & Hiscock, ). Here, we use targeted enrichment strategies implemented through Hyb‐Seq (Weitemier et al, ) to demonstrate its utility in understanding phylogenetic relationships of Hawaiian Cyrtandra, and to test morphologically‐based hypotheses of gene flow in this lineage.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns may reflect selection on wing length and breast colour, or on loci linked to these traits (Gay et al., ; Gompert, Lucas, Fordyce, Forister, & Nice, ; Larson et al., ), and we therefore infer a potential role for phenotypic divergence in maintaining isolation in secondary contact, as well as contributing to differentiation between subspecies (Safran, Scordato, et al., ). Simulations have shown that sharp phenotypic clines can emerge under models of secondary contact with neutral evolution if migration rates are low and sampling occurs relatively early in the contact history (Gompert & Buerkle, ). However, the observed clines are much narrower than would be expected under a model of neutral diffusion, even when considering a range of possible dispersal distances.…”
Section: Discussionmentioning
confidence: 99%
“…First, members of previously isolated lineages can hybridize freely (i.e., there is no reproductive isolation between taxa). This results in extensive gene flow; over time, phenotypes and genotypes will eventually become homogenous (Abbott et al., ; Gompert & Buerkle, ). Second, individuals from divergent populations can remain completely reproductively isolated (no gene flow, Coyne & Orr, ).…”
Section: Introductionmentioning
confidence: 99%
“…Information about gene flow has increased considerably thanks to the use of molecular markers and has also raised concerns on the potential dissemination of transgenes into landraces and wild types. The conclusion is that genes are transferred in all directions, both in allogamous and autogamous plants (Ellstrand et al, 1999, 2013; Jarvis and Hodgkin, 1999; Messeguer, 2003; Gompert and Buerkle, 2016), even though gene transfer can vary tremendously among species and populations, between plants within a population, and even over time (Ellstrand, 2014). Interestingly, after spontaneous crossing from commercial hybrids into some Italian landraces of maize, the introgressed genes have become the main targets for positive selection in farmers’ traditional management (Bitocchi et al, 2009, 2015).…”
Section: The Concept Of Landracementioning
confidence: 99%